2021
DOI: 10.3390/ani11061515
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Response to Australia’s Black Summer 2019–2020: The Role of a Zoo-Based Conservation Organisation in Wildlife Triage, Rescue, and Resilience for the Future

Abstract: Modern zoos are increasingly taking a leading role in emergency management and wildlife recovery. In the face of climate change and the predicted increase in frequency and magnitude of catastrophic events, zoos provide specialised expertise to assist wildlife welfare and endangered species recovery. In the 2019–2020 Australian bushfire season, now called Australia’s Black Summer, a state government-directed response was developed, assembling specialised individuals and organisations from government, non-govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…However, it must be recognised that during this initial period, there were also the highest proportions of koalas with negative outcomes. Parrott et al (2021) likewise reported a high number of wildlife euthanised at triage (20%) during the Victorian bushfires [ 11 ]. Despite this, humane euthanasia by veterinarians is preferable compared with animals dying, from a welfare perspective.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it must be recognised that during this initial period, there were also the highest proportions of koalas with negative outcomes. Parrott et al (2021) likewise reported a high number of wildlife euthanised at triage (20%) during the Victorian bushfires [ 11 ]. Despite this, humane euthanasia by veterinarians is preferable compared with animals dying, from a welfare perspective.…”
Section: Discussionmentioning
confidence: 99%
“…However, positive outcomes increased over the course of the bushfire response, when burn severity measures, poor body condition, and dehydration were decreasing in koalas presented at triage. Little is published of the outcomes of rescued koalas from previous bushfires; however, a recent study of wildlife rescued from the Black Summer bushfires in Victoria reported that 42% of rescued wildlife were released within 24 h of triage [ 11 ]. As release of KI koalas was more likely to occur for individuals triaged later in the bushfire response, it suggests that some koalas can find means to survive bushfires, despite minor burns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be high-profile and high-stakes when focused on charismatic megafauna or species that may harm humans, and involves considerable labor and financial resources (Molina-Loṕez et al, 2017;Englefield et al, 2019;Morgans et al, 2019;Haering et al, 2021). Scenarios prompting rescue-rehab-release vary and are typically reactive, stemming from catastrophic events posing danger to populations or creating unsuitable habitat [e.g., oil spills (Hong et al, 2020), algal blooms (Lefebvre et al, 2016), wildfires (Parrott et al, 2021), drought (Mo et al, 2021)]; and recurring threats that drive defaunation and compromise welfare [e.g., illegal wildlife trade (Moore et al, 2014;Castro Corteś et al, 2022), orphaning, injury, human-wildlife conflict (Marker et al, 2021)], or threats from occupying human-dominated areas [e.g. vehicle collisions, dog attacks (McAlpine et al, 2008;Kwok et al, 2021)].…”
Section: Introductionmentioning
confidence: 99%